2018
DOI: 10.15603/2176-1000/odonto.v24n48p25-37
|View full text |Cite
|
Sign up to set email alerts
|

Ação de própolis na superfície dentinária após condicionamento ácido

Abstract: Resumo: OBJETIVO - O própolis é conhecido por suas propriedades biológicas possuindo atividade anti-inflamatória, antibacteriana, cicatrizante e anestésica. Na odontologia este produto natural tem despertado interesse devido a resultados satisfatórios obtidos em diversas especialidades. Nosso estudo objetivou a avaliação ultraestrutural das alterações morfológicas provocadas pelo própolis sobre a superfície dentinária in vitro, após a remoção da camada de esfregaço com uma solução ácida. MÉTODOS  - Foram utili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The present study was directed towards the treatment of the dentin surface with a natural product, in order to follow a worldwide trend of finding alternative products in the treatment of oral health. The study was oriented with the use of propolis on the dental surface, because, as observed in the studies by Geraldini et al (2016), the formation of a barrier with this substance is possible, suggesting its permanence on the dentin surface, promoting the obliteration of dentinal tubules, thus being able to reduce DH.…”
Section: Resultsmentioning
confidence: 99%
“…The present study was directed towards the treatment of the dentin surface with a natural product, in order to follow a worldwide trend of finding alternative products in the treatment of oral health. The study was oriented with the use of propolis on the dental surface, because, as observed in the studies by Geraldini et al (2016), the formation of a barrier with this substance is possible, suggesting its permanence on the dentin surface, promoting the obliteration of dentinal tubules, thus being able to reduce DH.…”
Section: Resultsmentioning
confidence: 99%